(untitled) (BIRDEM Medical Journal, 2018)
Background: Kidney transplantation is the preferred treatment for end stage kidney disease (ESKD). Live related donor kidney transplant was started in BIRDEM General Hospital, Bangladesh, on 6th November 2004. The aim of this study was to share our last 10 years’ experience of live related donor kidney transplant. Methods: A questionnaire was formed and data were collected from the hospital records. We retrospectively evaluated patients’ clinical and laboratory findings. Results: A total of 111 live related donor kidney transplants were performed from 2004 to 2014. Male:female was 2.3:1. The mean age of the recipients was 37.45 ± 10.58 years. The causes of ESKD were chronic glomerulonephritis (CGN) (52, 46.9%), diabetes mellitus (DM) (31, 27.9%), hypertension (26, 23.4%), chronic pyelonephritis (1, 0.9%) and obstructive nephropathy (1, 0.9%). Pre-emptive transplantation was done in 4 (3.6%) patients. Patients on continuous ambulatory peritoneal dialysis and haemodialysis were 2 (1.8%) and 105 (94.6%) respectively. Most of the donors were siblings (55.9%). Majority (64.9%) had an uncomplicated recovery. The commonest complication during post-transplant hospital stay was infection (27.0%), mostly urinary tract infection (21.6%). Surgical failure was experienced in 1 (0.9%) and acute rejection was noted in 2 (1.8%) patients. Other complications were renal vein thrombosis (1, 0.9%), haemolytic uremic syndrome (1, 0.9%), acute tubular necrosis (1, 0.9%), peri-renal collection (1, 0.9%), pericardial effusion (1, 0.9%) and clot retention in urinary bladder (2, 1.8%). Mean post-transplant hospital stay was 12.39 ± 4.27 days. Mean duration from surgery to normalization of serum creatinine was 5.75 ± 4.15 days. During discharge, 71.2% patients had normal renal function (RF) with mean serum creatinine 1.03 ± 0.15 mg/dl and 26.1% patients had gradually improving RF with mean serum creatinine 2.01 ± 1.04 mg/dl. As induction, 61 (55%) patients received basiliximab and as maintenance therapy all patients received oral prednisolone, calcinurine inhibitor and mycophenolate. In the first year of transplant, 49.5% patients suffered from infections, of which urinary tract infection was the commonest (55.9%). Incidence of chronic allograft nephropathy in CGN, DM and hypertension patients were 25%, 19.4% and 23.1% respectively. Graft survival at 1 year, 3 years and 5 years was 94.06%, 85.88% and 77.27% respectively. Patient survival at 1 year, 3 years and 5 years was 98.1%, 88.24% and 84.09% respectively. Conclusions: Our results are comparable or in some aspects, even better in comparison to other centers of both developing and developed world. In a center of a developing country with limited facility and resource, these achievements are encouraging. Birdem Med J 2018; 8(3): 198-202